The sand-controlling and reservoir-controlling characteristics and exploration potential of the steep slope zone in the Huanghua Depression, Bohai Bay Basin, eastern China - Liu, Haitao; Chen, Yan; Wang, Jufeng; Sun, Deqiang; Tang, Zijun; Zhang, Chunming; Wu, Fengcheng; Jiang, Zhenglong (Frontiers in Earth Science, 2025)
As an important oil and gas exploration target area in continental rift basins, the sedimentary bodies in the steep slope zone are mainly composed of glutenite, featuring proximal and rapid accumulation, forming glutenite reservoirs with high porosity and permeability, which are conducive to the storage of oil and gas. The activities of boundary faults not only control the spatial structure of the basin but also affect the material source supply, paleogeomorphic morphology and the changes in the accommodation space within the basin. Through the study of the Nanpu and Banqiao trough areas and the Cangdong - Xi’nanzhuang - Baigezhuang steep slope zone in the Huanghua Depression, the influence of the supply capacity, groove transport flux and the structural form of the catchment area on the development scale of the glutenite fan bodies is discussed in detail. The research shows that the glutenite bodies in the steep slope zone are adjacent to the hydrocarbon-generating depression, forming a good source-reservoir contact hydrocarbon supply mode, presenting a deep adjacent-source reservoir-forming structure, with superior reservoir-forming conditions and the characteristics of being prone to forming lithologic oil and gas reservoirs; the Xi’nanzhuang steep slope zone is a multi-layer adjacent-source reservoir-forming structure, with equally superior reservoir-forming conditions, which can form both lithologic and structural oil and gas reservoirs; while the Baigezhuang steep slope zone, due to its relatively far distance from the hydrocarbon-generating depression, shows the characteristics of multi-layer far-source reservoir formation, with relatively poor reservoir-forming conditions, and is more inclined to form structural oil and gas reservoirs. Through the division of different structural styles such as shovel-shaped, slope-flat type and fault-step type steep slope zones and the in-depth analysis of their sand control and reservoir control mechanisms, the decisive role of factors such as fault activities, paleogeomorphology and material source supply on the development of glutenite fan bodies and the reservoir-forming rules of oil and gas in the steep slope zone has been clarified, which provides strong geological theoretical support for further improving the exploration efficiency and reserve prediction of glutenite oil and gas reservoirs in the steep slope zone of the Bohai Bay Basin.